INITIAL TRAINING IN PSYCHOLOGY AND ATTENTION TO SEXUAL VIOLENCE: REPORTS OF PROFESSIONALS - Tanaka, Brenda Sayuri [UNESP]; Thisoteine, George Miguel [UNESP]; Bortolozzi, Ana Claudia [UNESP] (Unesp-faculdade Ciencias & Letras, 2023)
Sexual violence is linked to health problems experienced by victims, and Psychology is critical in monitoring these people. This qualitative study investigated the contribution of initial training in Psychology in the care of cases of sexual violence, according to the reports of professionals. Five psychologists were interviewed whose reports were categorized using the content analysis method, resulting in the following groups: (1) Favorable experiences in training that helped in working with cases of sexual violence; (2) Specific difficulties when the complaint is sexual violence; (3) Gaps in initial training to work with cases of sexual violence; (4) Other factors that support current work with cases of sexual violence. The data indicate indirect contributions of the graduation to the work with victims of sexual violence, however, specific teachings planned for this action were not identified. It is concluded that there is a lack of specific content on sexual violence in the sample formation.
Keywords: Psychology; Training; Sexual violence; Assistance; Victims